Analysis on green technology system and LCA CO2 emission reduction of phase IIconstruction project of JDXG - J. Lu; J.J. Wu; Y. Zhou (International Association of Lowland Technology, 2016)
With rapid socio-economic development and the fast progression of urbanization, at present, China has become the world's largest energy consumers and carbon dioxide emitters, whose environment and resource faces enormous threatens and challenges. It is imperative that effective measures be taken to solve this problem. Green building in China has surely got a favorable development momentum over recent years, Assessment standard for green building (GB/T 50378-2014) (China Academy of Building Research, 2014) has been widely used in the evaluation work of the green building. In this paper, the case phase Ⅱ construction project of JDXG (Lingping, Hangzhou, China) has been rated as two-star green building by the standard. This project used plenty of green technology in energy conservation, water conservation, raw material conservation, land conservation and environmental optimization of interior space, and optimized the architectural design, which is expected to achieve significant effects, moreover, the green technology such as solar water heating system, spray irrigation system in landscape and high-ratio of green space would make significant contributions to carbon dioxide emission reduction in its life-cycle.